Aktivitetsbaserat-skällsord, mordeord eller framtid? : En socialpsykologisk studie om hur personal upplever det aktivitetsbaserade arbetssättet - Sällström, Sara (2016)
This is an investigation carried out in an office in Luleå who recantly implemented anew approach known as activity-based. The study presents the results from twelvesemi-structured interviews conducted with employees from the office. The aim of thestudy is to investigate how an activity-based workplace affect the staff's interactionwith each other and if it may have an impact on the psychosocial work environment.In this essay theories from Ervin Goffman and Randall Collins is used to analyse thefindings of the study. In addition to the theoretical framework, previous research ofrelevance is presented.The result shows that the activity-based workplace is perceived differently bydifferent people and that the main influencing factor is the individual's profession. Anegative attitude is most common among the employees and the arguments for this isthat the new approach leads to increased stress, anxiety and frustration. Validerat; 20160622 (global_studentproject_submitter)